FINGERPRINT KEYS ON MOTORCYCLES USING ARDUINO UNO R3 FINGERPRINT SENSOR - Wahyu Dwi Suharto (Universitas Islam Balitar, 2020)
Technological development and increasing human needs are two things that mutually influence one another, an additional security system that is better for both the user and the vehicle itself and is easy to use by the vehicle owner. One of the tools that can be used to help fulfill this security system is a fingerprint lock on a motorcycle using the Arduino uno r3 fingerprint sensor, a device made for motorized vehicle security systems using a fingerprint sensor to increase security on motorbike vehicles designed to use a relay. single channel as a link between hardware and software. With the increase in crime, especially motor vehicle theft today, it is not surprising that more and more people want a modern motorized vehicle security system that can secure their vehicles. To make a fingerprint lock tool on a motorcycle using the Arduino uno R3 fingerprint sensor, which is as follows, the Arduino uno R3, fingerprint sensor, single channel relay, and buzzer. Testing tools to determine whether or not a tool designed on a motorcycle using Arduino Uno R3 can be seen from the percentage obtained from testing the tool. Testing the fingerprint lock tool on a motorcycle using the Arduino uno R3 fingerprint sensor with a percentage of 68.8% of people who responded with a YES rating and 31.3% of people gave a NO response, it can be concluded that the tool can work well and the tool is able to help in the field of motorcycle safety Testing tools to determine whether or not a tool designed on a motorcycle using Arduino Uno R3 can be seen from the percentage obtained from testing the tool. Testing the fingerprint lock tool on a motorcycle using the Arduino uno R3 fingerprint sensor with a percentage of 68.8% of people who responded with a YES rating and 31.3% of people gave a NO response, it can be concluded that the tool can work well and the tool is able to help in the field of motorcycle safety Testing tools to determine whether or not a tool designed on a motorcycle using Arduino Uno R3 can be seen from the percentage obtained from testing the tool. Testing the fingerprint lock tool on a motorcycle using the Arduino uno R3 fingerprint sensor with a percentage of 50% of people who responded with a YES rating and 50% of people gave a NO response, it can be concluded that the tool can work well and the tool is able to help in the field of motorcycle safety.